(untitled) (Foro de Educacion, 2023)
For decades, Latin America has configured educational policies which placed equity at their core, with a view to reverse inequalities and move forward in building more just and inclusive societies. This article aims to trace an analytical path that allows us to reflect upon and problematize the linkages between the 2030 Agenda for Sustainable Development and educational equity policies in contemporary Mexico. Drawing upon documentary research of educational policies in Mexico during the presidential terms of Peña Nieto and López Obrador, this paper offers and answer to the following question: What are the focal points of the educational policies regarding equity in Mexico and what are their relationships to the 2030 Agenda? Research outcomes suggest a convergence of Mexican policies with the 2030 Agenda and to a certain continuity between the current and precedeing presidential terms, yet there is an array of key issues that remain underdeveloped or underdiscussed, which, need to be addressed in more detail if greater equity is to be achieved.